In Chronic Spontaneous Urticaria, Comorbid Depression Linked to Higher Disease Activity, and Substance P Levels - Memet, Bachar; Vurgun, Eren; Barlas, Fatma; Metz, Martin; Maurer, Marcus; Kocatürk, Emek (Frontiers in Psychiatry, 2021)
Background: Patients with chronic spontaneous urticaria often exhibit psychiatric comorbidities including depression that contribute to the impairment of their quality of life. How CSU and depression are linked isn’t well understood. Substance P has been shown to be increased in patients with CSU and is held to contribute to the pathogenesis of depression. Methods: We measured disease activity in 30 CSU patients without depression and 30 CSU patients with depression by using the urticaria activity score. The severity of depression was assessed with the Beck Depression Inventory. We measured SP levels in these patients as well as in 30 healthy control subjects. In patients with comorbid depression, we correlated SP levels with CSU disease activity and the severity of depression. Results: In CSU patients, disease activity and the severity of depression were positively linked. UAS7 values were higher in CSU patients with comorbid depression as compared to those without (p<0.05). SP levels were higher in CSU patients with depression than in those without (p<0.001), but was similar in all CSU patients compared to healthy controls. SP levels weren’t correlated with UAS7 values in CSU patients with depression, whereas they were weakly but significantly correlated with BDI scores (p<0.05). Conclusion: Our results suggest that, in CSU patients with comorbid depression, CSU disease activity affects the severity of depression. CSU patients with high disease activity should be explored for comorbid depression.